How does the intensity of physical therapy affect the Gross Motor Function Measure (GMFM-66) total score in children with cerebral palsy? A systematic review protocol - Mary Rahlin; Burris Duncan; Carol L Howe; Heidi L Pottinger (BMJ Open)
Introduction Intensive physical therapy (PT) interventions administered to children with cerebral palsy (CP) have received a significant amount of attention in published literature. However, there is considerable variability in therapy intensity among studies and notable lack of information on optimal intervention dosing. This makes it difficult for clinicians to use evidence to inform practice. Many studies use the Gross Motor Function Measure (GMFM-66) to assess functional progress in children with CP. The purpose of this systematic review will be to identify the GMFM-66 change score reported in published studies, with outcomes based on intervention intensity. Whether the type of PT intervention, child’s age, and Gross Motor Function Classification System level influence the GMFM-66 scores will be also assessed.Methods and analysis This systematic review protocol was developed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) 2015 checklist. In March 2018, nine databases (PubMed, Ovid MEDLINE, Cochrane Library, Embase, Scopus, Web of Science, CINAHL, ClinicalTrials.gov, and REHABDATA) were searched for controlled clinical trials and single-subject design studies of PT interventions of any kind and intensity that used the GMFM-66 as an outcome measure for children with CP, age up to 18 years. Two authors independently reviewed the titles and abstracts and arrived at consensus on paper selection for a full-text review. The same process was used for a full-text article screening based on further detailed inclusion criteria, with a final selection made for those suitable for data extraction. Prior to commencement of data extraction, all searches will be updated, and new results re-screened.Ethics and dissemination This study will involve a systematic review of published articles and no primary data collection. Therefore, no ethical approval will be necessary. Results will be disseminated in a peer-reviewed publication and presented at scientific conferences.PROSPERO registration number CRD42020147669